Gas Turbine Model Parameter Classification during Abnormal Operation Using Support Vector Machine for Maintenance - Yaw C.T.; Yap K.S.; Koh S.P.; Tiong S.K.; Ali K.; Low F.W. (Institute of Physics, 2023)
Electric power transmission; Gas turbines; Governors; Support vector machines; Abnormal operation; Gas turbine generators; Gas turbine modeling; Generator systems; MATLAB/ SIMULINK; Modeling parameters; Problem recognition; Simulink; Support vectors machine; Transmission systems; Simulink